SÍNTESE DE NANOPARTÍCULAS POLIMÉRICAS DE PLA-PEG CONTENDO MAGNETITA E RUTINA PARA UTILIZAÇÃO NAS ÁREAS BIOMÉDICAS - WATANABE, SILVANA HARUMI (2014)
Magnetic nanoparticles (MNP) like nanoparticles magnetite can to be guided through an external magnetic field, making possible the delivery of drugs when related to it, besides its low toxicity and easy obtaining. Facing this possibility of applicability, the first step of this work it consists of in the synthesis of nanoparticles magnetite by the modified sol-gel method, and characterizations by X-ray diffraction and magnetic analysis. The second step is related to the incorporation of nanoparticles magnetite and rutin in polymeric nanoparticles of polylactic acid (PLA) and polyethylene acid (PEG), aiming the protection and directed delivery drug. Among many of the pharmacological uses, the rutin is highlighted by the antioxidant power, disadvantaged by its low solubility in an aqueous medium, related to the possible degradation in the time. Aiming to develop an optimized formulation of the polymeric nanoparticles by using the technique of emulsion evaporation of the solvent, many parameters of the formulation are independently changed among these parameters: the concentration of the surfactant (PVA), the polymers (PLA and PEG), as well as the solvents of the oily phase averaging between 1356 to 241 nm inside and the efficiency of encapsulation between 45 to 75% without losing any magnetic property were obtained. In the evaluation of the antioxidant potential by using the method of the radical ABTS, it has been verified that the polymeric nanoparticles obtained a better efficiency in the inhibition compared to the free rutin, resulting on a significant raise of IC50. Suggesting a longer lrealese and protection against the degradation of the rutin drug, respectively. Studies show that the polymeric nanoparticles can be used as efficient liberation system and directing the rutin drug with antioxidant potential.